Real-world adherence trajectories to direct oral anticoagulants in naive patients with atrial fibrillation in Spain - Leguízamo-Martínez, L. M.; Ballarin, M. E.; Hurtado, I.; Sanfélix-Gimeno, G.; Sánchez-Sáez, F.; Sabaté, M. (Frontiers in Pharmacology, 2025)
AimsThis study aimed to identify adherence trajectories and associated factors in atrial fibrillation patients who initiated direct oral anticoagulant (DOAC) therapy, using population-based data from the Catalonia and Valencia regions in Spain during a 2-year follow-up.Methods and ResultsGroup-based trajectory modelling (GBTM) was applied to assess adherence patterns in cohorts comprising 14,641 patients in Catalonia and 13,211 in Valencia. Adherence trajectories were categorised based on prescription data, revealing three main trajectories in Valencia and five in Catalonia. Most patients in Valencia demonstrated high adherence, whereas Catalonia showed more varied patterns, including early, gradual, and late declines. Factors associated with non-adherence included high co-insurance levels, alcohol use, and specific DOACs, such as dabigatran.ConclusionAdherence trajectories differed between the two regions, with three identified in Valencia and five in Catalonia. Shared non-adherence patterns were observed across both cohorts, while Catalonia exhibited additional noncompliance trends. Key factors associated with non-adherence included socio-economic variables, clinical characteristics, and the type of DOAC prescribed. Understanding these patterns is essential for developing targeted intervention strategies to improve adherence and optimise treatment outcomes.